Impact in oral health and the prevalence of temporomandibular disorder in individuals with Parkinson’s disease - Fernandes, Kristianne Porta Santos; Bussadori, Sandra Kalil; Biasotto-Gonzalez, Daniela Aparecida; Paula Fernanda da Costa Silva; Ferrari, Raquel Agnelli Mesquita; Motta, Lara Jansiski; Silva, Soraia Micaela (Journal of Physical Therapy Science, 2015)
[Purpose] The aims of the present study were to investigate the prevalence of temporomandibular disorder (TMD) in a group of patients with Parkinson’s disease (PD), and to analyze oral health according to the severity of the disease. [Methods] Signs and symptoms of TMD were evaluated using the Research Diagnostic Criteria for Temporomandibular Disorders, and oral health impact was measured using the Oral Health Impact Profile. The unpaired Student’s t-test was used to compare groups with and without TMD. Pearson’s correlation coefficients were calculated to determine correlations between the level of functional independence and oral health impact. Fisher’s exact test was used to test the association between TMD and the severity of symptoms of PD. [Results] Fifty-nine individuals with PD were analyzed. The prevalence of TMD was 20.33%. No statistically significant associations were found between TMD and the severity of PD. Oral health impact was considered weak, but a statistically significant difference between groups with and without TMD was found for psychological disability (p = 0.003). No significant correlation was found between the level of functional independence and oral health impact. [Conclusion] The prevalence of TMD among patients with Parkinson’s disease was 20.33%. A statistically significant difference between groups with and without TMD was found regarding the psychological disability domain.